Indium joints for cryogenic gravitational wave detectors. (3rd December 2015) - Hofmann, G; Chen, D; Bergmann, G; Hammond, G D; Hanke, M; Haughian, K; Heinert, D; Hough, J; Khalaidovski, A; Komma, J; Lück, H; Majorana, E; et al.
Abstract: A viable technique for the preparation of highly thermal conductive joints between sapphire components in gravitational wave detectors is presented. The mechanical loss of such a joint was determined to be as low as 2 × 10 −3 at 20 K and 2 × 10 −2 at 300 K. The thermal noise performance of a typical joint is compared to the requirements of the Japanese gravitational wave detector, KAGRA. It is shown that using such an indium joint in the suspension system allows it to operate with low thermal noise. Additionally, results on the maximum amount of heat which can be extracted via indium joints are presented. It is found that sapphire parts, joined by means of indium, are able to remove the residual heat load in the mirrors of KAGRA.